Owl at home - Lobel, Arnold (New York : Harper & Row, 1975)
Relates five adventures of Owl.
Wilson's Children
Elem. School Library Collection
Notable/Best Books (A.L.A.)
2.5
K-3.
Keywords: Owls -- Fiction; Owls -- Fiction